2005
DOI: 10.1590/s0100-69912005000600009
|View full text |Cite
|
Sign up to set email alerts
|

Reabertura do piloro gastroduodenal após sua cerclagem, em ratos

Abstract: RESUMO: Objetivos:A lesão duodenal é um evento pouco freqüente, que incide em 3% a 12% dos pacientes com trauma de abdome. A sutura dessa ferida e a drenagem adequada da região é o tratamento mais utilizado nas lesões menores. Entretanto, as feridas de maior dimensão continuam sendo um desafio para a escolha do melhor tratamento. O fechamento do piloro e o desvio do trânsito digestório por meio de anastomose gastrojejunal é a conduta mais freqüente nessas situações. Os objetivos deste estudo foram verificar se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…19 In an experimental study on 30 rats subjected to pyloric exclusion with different occlusion suture materials and gastrojejunostomy with or without vagotomy, it was observed that nonabsorbable sutures maintained the pyloric closure for a longer duration (36.3 ± 11.6 days) and that vagotomy reduced the gastric inflammation without influencing the time when the pylorus should be reopened. 21 In another study from our laboratory, Pierro et al 12 compared the results from primary repair versus repair associated with pyloric exclusion and gastrojejunostomy to treat complex duodenal injuries in 24 dogs. They did not observe any differences in the incidence of duodenal stenosis, fistula formation, intraabdominal abscess or death between the two groups, but pyloric exclusion was a longer and more traumatic procedure, and it resulted in greater weight loss and increased incidence of vomiting among the animals.…”
Section: Discussionmentioning
confidence: 99%
“…19 In an experimental study on 30 rats subjected to pyloric exclusion with different occlusion suture materials and gastrojejunostomy with or without vagotomy, it was observed that nonabsorbable sutures maintained the pyloric closure for a longer duration (36.3 ± 11.6 days) and that vagotomy reduced the gastric inflammation without influencing the time when the pylorus should be reopened. 21 In another study from our laboratory, Pierro et al 12 compared the results from primary repair versus repair associated with pyloric exclusion and gastrojejunostomy to treat complex duodenal injuries in 24 dogs. They did not observe any differences in the incidence of duodenal stenosis, fistula formation, intraabdominal abscess or death between the two groups, but pyloric exclusion was a longer and more traumatic procedure, and it resulted in greater weight loss and increased incidence of vomiting among the animals.…”
Section: Discussionmentioning
confidence: 99%
“…5 é um dos procedimentos que mais têm sido estudados ultimamente, tanto do ponto de vista clínico quanto experimental 2,[7][8][9][10][11][16][17][18][19] . Graham e col. 7 relataram 68 casos de lesões duodenopancreáticas, sendo 32 delas tratadas pelo método de exclusão pilórica e gastrojejunostomia.…”
unclassified